Global Research Landscape of Hybrid Agile-Lean Methodologies in Information Systems Development - Supina Batubara; Aslina Binti Saad; Fanny (CV. Raskha Media Group, 2026)
The rapid expansion of the global digital economy necessitated high operational efficiency and structural flexibility in information systems development (ISD). Traditional software engineering methodologies frequently failed to cope with volatile market demands, leading to elevated project failure rates in organizational and institutional ecosystems. Although hybrid agile-lean frameworks emerged as a promising integration to balance market responsiveness and resource waste elimination, a comprehensive structural mapping of this domain remained scarce. This study investigated the global research trends, core thematic clusters, and evolutionary trajectories of hybrid agile-lean adoption in ISD. A bibliometric analysis was conducted using the Scopus database to retrieve relevant peer-reviewed literature published between 2010 and 2023. VOSviewer software was applied to analyze key performance indicators, keyword co-occurrences, network densities, and chronological overlay visualizations. The empirical results mapped the domain into four primary thematic networks: technology and development, innovation performance, methodology adoption, and entrepreneurship education. The chronological trend revealed a massive shift from traditional rekayasa software structures toward contemporary digital transformation capabilities and research commercialization. Most importantly, the density visualization exposed a significant literature gap regarding hybrid methodological adoption inside highly bureaucratic environments, academic institutions, and developing regions like Indonesia. These findings provided a systematic justification and roadmap for future studies to engineer adaptive system architectures within non-traditional business settings.